1998
DOI: 10.1016/s0014-5793(98)01059-x
|View full text |Cite
|
Sign up to set email alerts
|

ATP‐dependent copper transport by the Menkes protein in membrane vesicles isolated from cultured Chinese hamster ovary cells

Abstract: The Menkes (MNK) protein is a vital component of copper homeostasis in mammalian cells. In this paper we provide the first biochemical evidence that the MNK protein functions as a copper-translocating P-type ATPase in mammalian cells. The enzyme activity in membrane vesicles prepared from Chinese hamster ovary cells overexpressing MNK was ATP-dependent, correlated with the amount of MNK and followed MichaelisMenten kinetics with respect to copper. The copper transport was observed only under reducing condition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
52
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(63 citation statements)
references
References 44 publications
11
52
0
Order By: Relevance
“…This value is similar to that observed with other thermophilic enzymes (33,54) and much higher that the 20 -40 kJ/mol energy of activation determined for mesophilic enzymes (46). Previous studies have indicated the dependence of CPxATPase activity on the presence of thiolates (20,30) and/or reducing agents (55,56). The CopA Ag-ATPase activity showed a strong dependence on cysteine concentration with maximum activity at 20 mM cysteine (Fig.…”
Section: Characterization Of a Thermophilic Agsupporting
confidence: 89%
“…This value is similar to that observed with other thermophilic enzymes (33,54) and much higher that the 20 -40 kJ/mol energy of activation determined for mesophilic enzymes (46). Previous studies have indicated the dependence of CPxATPase activity on the presence of thiolates (20,30) and/or reducing agents (55,56). The CopA Ag-ATPase activity showed a strong dependence on cysteine concentration with maximum activity at 20 mM cysteine (Fig.…”
Section: Characterization Of a Thermophilic Agsupporting
confidence: 89%
“…Here, we show that copper thiolate is also a putative substrate for the cucumber homolog of HMA5 pumps. Contrary to Cys, the positive effect of reducing agents on copper ATPase activity probably results from their action on the copper redox state (47,48). Reducing agents appear to be necessary to keep copper in a reduced state, a form activating phosphorylation of copper ATPases.…”
Section: Discussionmentioning
confidence: 99%
“…Then, cells were fixed in uranyl acetate and in OsO 4 , dehydrated through a graded series of ethanol and embedded in the epoxy resin (Epon 812). Thin sections were cut with Leica EM UC6 ultramicrotome (Leica Microsystems, Wetzlar, Germany).…”
Section: Nmr Analysis Of N-atp7b-thementioning
confidence: 99%